Complete mitochondrial genome of Bactrocera arecae (Insecta: Tephritidae) by next-generation sequencing and molecular phylogeny of Dacini tribe - Yong, Hoi Sen; Song, Sze Looi; Lim, Phaik Eem; Chan, Kok Gan; Chow, Wan Loo; Eamsobhana, Praphathip (Nature Research, 2015)
The whole mitochondrial genome of the pest fruit fly Bactrocera arecae was obtained from next-generation sequencing of genomic DNA. It had a total length of 15,900 bp, consisting of 13 protein-coding genes, 2 rRNA genes, 22 tRNA genes and a non-coding region (A + T-rich control region). The control region (952 bp) was flanked by rrnS and trnI genes. The start codons included 6 ATG, 3 ATT and 1 each of ATA, ATC, GTG and TCG. Eight TAA, two TAG, one incomplete TA and two incomplete T stop codons were represented in the protein-coding genes. The cloverleaf structure for trnS1 lacked the D-loop, and that of trnN and trnF lacked the TΨC-loop. Molecular phylogeny based on 13 protein-coding genes was concordant with 37 mitochondrial genes, with B. arecae having closest genetic affinity to B. tryoni. The subgenus Bactrocera of Dacini tribe and the Dacinae subfamily (Dacini and Ceratitidini tribes) were monophyletic. The whole mitogenome of B. arecae will serve as a useful dataset for studying the genetics, systematics and phylogenetic relationships of the many species of Bactrocera genus in particular, and tephritid fruit flies in general.